2018
DOI: 10.1007/s00709-018-1235-z
|View full text |Cite
|
Sign up to set email alerts
|

Ion homeostasis, osmoregulation, and physiological changes in the roots and leaves of pistachio rootstocks in response to salinity

Abstract: Pistachio, one of the important tree nuts, is cultivated in arid and semi-arid regions where salinity is the most common abiotic stress encountered by this tree. However, the mechanisms underlying salinity tolerance in this plant are not well understood. In the present study, five 1-year-old pistachio rootstocks (namely Akbari, Badami, Ghazvini, Kale-Ghouchi, and UCB-1) were treated with four saline water regimes (control, 8, 12, and 16 dS m) for 100 days. At high salinity level, all rootstocks showed decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 69 publications
3
43
0
Order By: Relevance
“…This finding opens a new avenue, where GB is associated with symbiosis to regulate abiotic stress tolerance in plants. Glycinebetaine, Pro, total phenolics and soluble carbohydrate content sharply increased in the rootstock and leaves of pistachio plants on exposure to salt stress [87]. The accumulation of the osmolytes also facilitated exclusion of Na + and Clin the rootstocks of the assayed cultivars grown under saline conditions [87].…”
Section: Saltmentioning
confidence: 99%
“…This finding opens a new avenue, where GB is associated with symbiosis to regulate abiotic stress tolerance in plants. Glycinebetaine, Pro, total phenolics and soluble carbohydrate content sharply increased in the rootstock and leaves of pistachio plants on exposure to salt stress [87]. The accumulation of the osmolytes also facilitated exclusion of Na + and Clin the rootstocks of the assayed cultivars grown under saline conditions [87].…”
Section: Saltmentioning
confidence: 99%
“…Salt stress caused the inhibition of photosynthesis-related pigments in plants, and further impacted on the photosynthesis efficiency [45,46]. Our data showed that the chlorophyll level in transgenic tobacco plants is always higher than WT plants subjected to salt stress ( Figure 6A).…”
Section: Discussionmentioning
confidence: 68%
“…Compatible cytosolutes including proline, TNC, soluble sugars and glycine betaine can reduce the cell's osmotic potential under dehydration (Sheikh-Mohamadi et al, 2017d). Proline is an important compatible osmolyte and a scavenger of ROS in plants (Akbari et al, 2018). During the experiment, proline content remained constant at optimal temperatures in all ecotypes (Fig.…”
Section: Resultsmentioning
confidence: 91%